Model Pendampingan Academic Writing Clinic untuk Meningkatkan Kesiapan Publikasi Ilmiah Calon Guru - Suci Yuniati (Dharma: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve students' capacity in writing scientific articles worthy of publication in national journals. Problems faced by prospective teachers include a poor understanding of the structure of scientific articles, limited literature synthesis skills, and a lack of knowledge about ethics and publication procedures. The implementation method uses a participatory and applied approach through several stages, namely preparation, scientific article writing workshops, intensive small-group-based mentoring, review, and evaluation. The subjects of the activity were 22 prospective teachers in the fourth semester of the Mathematics Education Bachelor Program who were preparing to compile their final project research. The results of the activity showed a 31.8% increase in participants successfully publishing articles in national journals after participating in mentoring. This activity has a positive impact on fostering a culture of writing and scientific publication among prospective teachers in higher education.